Generating a host range-expanded recombinant baculovirus - Wu, C. F.; Deng, Z. H.; Long, Z.; Cai, Y.; Ying, Z. F.; Yin, H. Q.; Yuan, M. J.; Clem, Rollie J.; Yang, K.; Pang, Y. (My University, 2017)
As baculoviruses usually have a narrow insecticidal spectrum, knowing the mechanisms by which they control the host-range is prerequisite for improvement of their applications as pesticides. In this study, from supernatant of culture cells transfected with DNAs of an Autographa californica multiple nucleopolyhedrovirus (AcMNPV) mutant lacking the antiapoptotic gene p35 (vAc(Delta P35)) and a cosmid representing a fragment of Spodoptera exigua nucleopolyhedrovirus (SeMNPV), a viral strain was plaque-purified and named vAcRev. vAcRev had a broader host range than either vAc(Delta P35) or SeMNPV parental virus, being able to infect not only the permissive hosts of its parental viruses but also a nonpermissive host (Spodoptera litura). Genome sequencing indicated that vAcRev comprises a mixture of two viruses with different circular dsDNA genomes. One virus contains a genome similar to vAc(Delta P35), while in the other viral genome, a 24.4 kbp-fragment containing 10 essential genesis replaced with a 4 kbp-fragment containing three SeMNPV genes including a truncated Se-iap3 gene. RNA interference and ectopic expression assays found that Se-iap3 is responsible for the host range expansion of vAcRev, suggesting that Se-iap3 inhibits the progression of apoptosis initiated by viral infection and promotes viral propagation in hosts both permissive and non-permissive for AcMNPV and SeMNPV.
Citation: Wu, C. F., Deng, Z. H., Long, Z., Cai, Y., Ying, Z. F., Yin, H. Q., . . . Pang, Y. (2016). Generating a host range-expanded recombinant baculovirus. Scientific Reports, 6, 14. doi:10.1038/srep28072
Keywords: Nuclear Polyhedrosis-Virus; Autographa-Californica Nucleopolyhedrovirus; Spodoptera-Littoralis-Nucleopolyhedrovirus; Vitripennis Walker; Hymenoptera; Lepidopteran Cell-Lines